2019
DOI: 10.1093/infdis/jiy719
|View full text |Cite
|
Sign up to set email alerts
|

Infection Studies in Pigs and Porcine Airway Epithelial Cells Reveal an Evolution of A(H1N1)pdm09 Influenza A Viruses Toward Lower Virulence

Abstract: We analyzed the virulence of pandemic H1N1 2009 influenza A viruses in vivo and in vitro. Selected viruses isolated in 2009Selected viruses isolated in , 2010Selected viruses isolated in , 2014Selected viruses isolated in , and 2015 were assessed using an aerosol-mediated high-dose infection model for pigs as well as air-liquid interface cultures of differentiated airway epithelial cells. Using a dyspnea score, rectal temperature, lung lesions, and viral load in the lung as parameters, the strains from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Results obtained from infection of ALI cultures by influenza viruses have relevance also for understanding natural infections. Pathogenicity was found to be correlated with the loss of ciliated cells in infection of ALI cultures [25][26][27], i.e. the more pathogenic viruses showed an enhanced virulence in ALI cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from infection of ALI cultures by influenza viruses have relevance also for understanding natural infections. Pathogenicity was found to be correlated with the loss of ciliated cells in infection of ALI cultures [25][26][27], i.e. the more pathogenic viruses showed an enhanced virulence in ALI cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Explants and air-liquid interface (ALI) cultures of respiratory epithelium represent to a great extent the natural site of infection of respiratory viruses and are broadly used to study the infection biology of many viruses including IAVs, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and respiratory syncytial virus (RSV) [ 46 48 ]. Regarding IAVs, back to back infections of pigs and ALI-cultures derived from pigs with different isolates of pdmH1N1 showed that the infection phenotype of ALI-cultures can be used to predict in vivo virulence [ 49 ]. Importantly, as explants lack any component of adaptive immunity, they allow to evaluate virus-cell interactions at the natural site of infection, excluding systemic responses and/or fitness effects resulting from antigenic drift.…”
Section: Discussionmentioning
confidence: 99%
“…This infection model is also characterized by a loss of ciliated cells and it has been shown that the infected ciliated cells undergo apoptosis. Another similarity of the viral and the bacterial infection model is that the loss of ciliated cells is not associated with a loss of the barrier function of the epithelial cell layer [ 27 , 31 , 41 ]. Neither ions nor macromolecules can pass via the paracellular route from the apical to the basolateral side of the cells.…”
Section: Discussionmentioning
confidence: 99%